Structure Design and Performance Analysis for Direct-driving Automated Mechanical Transmission - Yu Xiao; Li Bo; Ge Wenqing; Li Zhengping (Jixie chuandong)
To shorten the transmit route of shift force,improve transmission efficiency,a kind of electromagnetic direct-drive transmission（ D-AMT） is proposed,in which the actuator could drive sleeve shift directly for shifting. The finite element analysis model is established in JMAG to optimize the structure of actuator,the math model of shifting,researched the shifting parameters of D-AMT is established,the influence factors of shifting is analyzed and the influence of shift parameters on shifting performance is researched. The results show that the mass of actuator is 1. 313 kg,which decreased 26% compared with conventional AMT. At the typical working condition of pure electric vehicle（ difference of rotary speed is 500 r/min and the moment of inertia is0. 1 kg·m2）,time for shift is 0. 29 s,the shift shocks are 4. 9 m/s3 and 0. 695,which meet the requirement of shifting. The D-AMT provide a new program of the transmission innovation,which will develop pure electric dynamic transmission technology.